Analisis Komponen Literasi Sains pada Buku Teks Biologi SMA/Ma Kelas X - Marsyah, Shafira Hana; Manalu, Kartika; Rambe, Riris Nurkholidah (Jurnal Simki Pedagogia, 2023)
This study aims to analyze the category of scientific literacy in class X biology textbooks at MAS Nurul Iman Mahato. The research used in this research uses a qualitative approach with content analysis. Content analysis is commonly used in analyzing the validity of the contents of a book to draw conclusions from the contents of books and documents using certain procedures. This research was conducted at MAS Nurul Iman located in Mahato Bandar Selamat Village, North Tambusai District, Rokan Hulu Regency, Riau Province with biology textbooks for class X in MAS Nurul Iman Mahato. Data collection used using interview and observation techniques. Analyzing the data obtained, the steps taken to obtain analysis data from the data that have been obtained by 1) Summing the occurrence of scientific indicators from each component of the scientific literacy category, 2) Calculating the percentage of occurrence of scientific literacy indicators in the books being analyzed 3) Calculating the reliability of the data 4) Draw Conclusions. From the results of the research discussed earlier, it can be concluded that there are several percentages of the appearance of the scientific literacy category in class X biology textbooks at MAS Nurul Iman Mahato. Viewed from the aspect of science as the body of knowledge, the presentation of scientific literacy in class X biology textbooks in MAS Nurul Iman Mahato of 46.68%, seen from the aspect of science as a way of knowledge that the presentation of scientific literacy in class X biology textbooks at MAS Nurul Iman Mahato is 19.55%, viewed from the aspect of science as a way of thinking that the presentation of scientific literacy in class X biology textbooks at MAS Nurul Iman Mahato by 13.30%, seen from the aspect of science as an aspect of science interaction with technology and social that the presentation of scientific literacy in class X biology textbooks at MAS Nurul Iman Mahato is 13.99 %.